Family reunion in the Barcelona province, 2004-2008 - Domingo, Andreu; López-Falcón, Diana; Bayona i Carrasco, Jordi (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The Barcelona Province, at 1 January 2008, concentrates around to 14% of the registered foreign population and approximately one third of the granted family reunion applications of Spain. In this paper, we analyze from a demographic perspective the 67,493 granted family reunion applications that were processed at the Government Sub-Delegation in Barcelona, in the period between January 2004 and April 2008. In our text we demonstrate how the different migratory strategies based on gender roles become relevant in order to study the profile of the 34,025 reunificators and the 64,665 effective reunifications. This fact clearly shows the complementarity between family reunion and the original migration project. At the same time, we have analyzed the temporary incidence between the application and the effective execution of the family reunification permit. Finally, an approximation of what we might call factual family reunions have been made while comparing the effective reunions and the immigrants coming from abroad data of the Residential Variation Statistic (INE) during the period of analysis